HUMAN RIGHTS COMMITTEE AND UZBEKISTAN: THE ISSUES OF IMPLEMENTATION OF INTERNATIONAL OBLIGATIONS (World Bulletin of Management and Law, 2024)
This work presents analytical opinions on the International Covenant on Civil and Political Rights and the procedures for its realisation, the activities of the Human Rights Committee and the participation of Uzbekistan in it.